Factors Influence on Non Performing Financing Islamic Banking - Nurul Dewi Annisa; Nur Isna Inayati (Islamic Accounting Journal, 2022)
The purpose of this study was to examine the effect of Capital Adequacy Ratio, Financing To Deposit Ratio, Operating Costs, Operating Income and Inflation on Non-Performing Financing. This type of research uses quantitative methods with secondary data whose data collection is through the website of each BUS registered with the OJK during the research period. The analytical method used is Moderated Regression Analysis which is calculated by Eviews 9. The results of this study indicate that partially the CAR, FDR, BOPO and Inflation variables have a significant positive effect on NPF. Meanwhile, simultaneously CAR and BOPO have no effect on NPF, while FDR and Inflation have a significant positive effect on NPF. Inflation as a moderating variable is able to strengthen the effect of CAR on NPF, but is also able to weaken the relationship between FDR and inflation, but inflation also cannot moderate the effect of BOPO on NPF.Keywords: CAR, FDR, BOPO, Inflation and NPF